Imobilisasi Tembaga (Cu) dan Netralisasi Aktivitas Ion Hidrogen (pH) pada Limbah Cair Industri Peleburan Emas Dengan Batu Gamping (Limestone) - Setiani, Onny; Raharjo, Mursid; Hanani, Yusniar; Budiyono, Budiyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2002)
The objectives of this research were to determine the effectiveness of limestones in neutralizing hydrogen ion activity (pH), immobilizing cooper (Cu) and to implement a waste water treatment process from the gold molten industry using a cost-effective method to prevent the environment contamination from hazardous wastes. Before implementing technology, a preliminary study was done to determine a simple and cost effective method to neutralize pH, immobilize and sedimentation of Copper (Cu) using limestones (CaCO3). The results of laboratory examination in preliminary study showed that limestones may decrease the concentration of Cu from 23,070 mg/L to 0.711 mg/L, TDS from 30,302 mgLl to 18,289 mg/L and neutralize pH from 1.0-3.0 to 7.0. This research demonstrate that limestones may provide a cost effective method to immobilize Cu and neutralize contaminated wastewater of the gold molten industry. Since the technology is very simple, it is suggested to be used by home scale or small industry to protect the environment from toxic waste pollution. Keywords: Immobilizing cooper, lime stone, neutralization, waste water.